1991
DOI: 10.1159/000181874
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism and Pericardial Effusion

Abstract: A group of infants, affected by congenital hypothyroidism diagnosed through the neonatal screening program, was investigated with echocardiography to detect the presence of pericardial effusion. We studied the relationship between the effusion and the etiology of hypothyroidism, established through thyroid scintiscanning. Our data show a high prevalence of effusion in hypothyroid patients, without other clinical signs of cardiac involvement as well as a relationship between the etiology of hypothyroidism and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Accordingly, growth was markedly retarded in cases 2 and 3. Minor pericardial effusion, however, may develop more rapidly as suggested by echocardiographic studies in newborns with congenital hypothyroidism [1,10]. Although growth delay and excessive weight gain, which both suggest thyroid dysfunction, are often present in hypothyroid children with Down syndrome, they are easily overlooked unless specific growth charts are used [2].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, growth was markedly retarded in cases 2 and 3. Minor pericardial effusion, however, may develop more rapidly as suggested by echocardiographic studies in newborns with congenital hypothyroidism [1,10]. Although growth delay and excessive weight gain, which both suggest thyroid dysfunction, are often present in hypothyroid children with Down syndrome, they are easily overlooked unless specific growth charts are used [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that hypothyroidism can lead to a pericardial effusion. [5][6][7] Also, triiodothyronine is essential for maintaining cardiac contractility and relaxation, appropriate systemic vascular resistance, and normal cardiac ion channels. 14 In addition, severe hypothyroidism is associated with a decrease in myocardial contractility, increased systemic vascular resistance, and clinical heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…15 All of these abnormalities can be reversed with thyroid hormone therapy. [5][6][7][8]15 Digoxin treatment can control CHF in this situation. Nevertheless, there is a high risk for digitalis intoxication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation